Mechanisms Underlying the Functional Cooperation Between PPARα and GRα to Attenuate Inflammatory Responses - Bougarne, Nadia; Mylka, Viacheslav; Ratman, Dariusz; Beck, Ilse M.; Thommis, Jonathan; De Cauwer, Lode; Tavernier, Jan; Staels, Bart; Libert, Claude; De Bosscher, Karolien (Frontiers in Immunology, 2019)
Glucocorticoids (GCs) act via the glucocorticoid receptor (NR3C1, GRalpha) to combat overshooting responses to infectious stimuli, including lipopolysaccharide (LPS). As such, GCs inhibit the activity of downstream effector cytokines, such as tumor necrosis factor (TNF). PPARalpha (NR1C1) is a nuclear receptor described to function on the crossroad between lipid metabolism and control of inflammation. In the current work, we have investigated the molecular mechanism by which GCs and PPARalpha agonists cooperate to jointly inhibit NF-κB-driven expression in A549 cells. We discovered a nuclear mechanism that predominantly targets Mitogen- and Stress-activated protein Kinase-1 activation upon co-triggering GRalpha and PPARalpha. In vitro GST-pull down data further support that the anti-inflammatory mechanism may additionally involve a non-competitive physical interaction between the p65 subunit of NF-κB, GRalpha and PPARalpha. Finally, to study metabolic effector target cells common to both receptors, we overlaid the effect of GRalpha and PPARalpha crosstalk in mouse primary hepatocytes under LPS-induced inflammatory conditions on a genome-wide level. RNA-seq results revealed lipid metabolism genes that were upregulated and inflammatory genes that were additively downregulated. Validation at the cytokine protein level finally supported a consistent additive anti-inflammatory response in hepatocytes.